Environmental activism: a reference handbook - Switzer, Jacqueline Vaughn (Contemporary world issues, 2003)
Publisher description: Beginning with an overview of activism in the past century from 1900 to 2001, Environmental activism: a reference handbook puts organizations and their activities into historical context. This volume offers both an American perspective and a global perspective. It chronicles the major events that sparked environmental actions; aligns individuals with organizations, such as John Muir and the Sierra Club; and presents a balanced treatment of activities in both conservative and liberal political spheres. Separate chapters identify six eras of activism from 1900 to 2001 and include their characteristics, issues, strategies, and advocates. This is followed by summaries of the various types of organizations and their strategies, including direct action (ecoterrorism, monkey wrenching) as well as mainstream activity (lobbying, letter writing)